2016
DOI: 10.1038/ismej.2016.152
|View full text |Cite
|
Sign up to set email alerts
|

Tick microbiome and pathogen acquisition altered by host blood meal

Abstract: Lyme disease, a zoonotic disease, is the most prevalent vector-borne disease in the Northern Hemisphere. Diversity of the vector (tick) microbiome can impact pathogen transmission, yet the biotic and abiotic factors that drive microbiome diversity are largely unresolved, especially under natural, field conditions. We describe the microbiome of Ixodes pacificus ticks, the vector for Lyme disease in the western United States, and show a strong impact of host blood meal identity on tick microbiome species richnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
182
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(203 citation statements)
references
References 24 publications
10
182
1
2
Order By: Relevance
“…In addition, they carry numerous endosymbionts and commensals, which may provide nutrient supplements to the tick and also affect vector competence (reviewed in (Narasimhan & Fikrig, ; Bonnet et al., ; Clay & Fuqua, )). Studies have reported that the tick microbial community is variable depending on several factors such as source of host blood meal (Rynkiewicz, Hemmerich, Rusch, Fuqua, & Clay, ), feeding status (Menchaca et al., ; Swei & Kwan, ; Zhang et al., ), tick species, life stage, gender, and geographical origin (Carpi et al., ; Van Treuren et al., ; Williams‐Newkirk, Rowe, Mixson‐Hayden, & Dasch, ). However, very few studies have focused on the tick microbiome differences based on environmental conditions such as seasons of collection (Lalzar, Harrus, Mumcuoglu, & Gottlieb, ) or the immediate environment (Menchaca et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they carry numerous endosymbionts and commensals, which may provide nutrient supplements to the tick and also affect vector competence (reviewed in (Narasimhan & Fikrig, ; Bonnet et al., ; Clay & Fuqua, )). Studies have reported that the tick microbial community is variable depending on several factors such as source of host blood meal (Rynkiewicz, Hemmerich, Rusch, Fuqua, & Clay, ), feeding status (Menchaca et al., ; Swei & Kwan, ; Zhang et al., ), tick species, life stage, gender, and geographical origin (Carpi et al., ; Van Treuren et al., ; Williams‐Newkirk, Rowe, Mixson‐Hayden, & Dasch, ). However, very few studies have focused on the tick microbiome differences based on environmental conditions such as seasons of collection (Lalzar, Harrus, Mumcuoglu, & Gottlieb, ) or the immediate environment (Menchaca et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Microclimatic conditions may affect microbial occurrence directly, or indirectly via affecting tick behavior or host community composition [86, 87]. Furthermore, topography can affect population connectivity and dispersal in metapopulation networks [88].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of ticks removed from wildlife hosts comes with the inherent complication of a blood meal. The host blood meal has recently been shown to affect both the tick microbiome composition and the presence of pathogens (Landesman et al, 2019;Swei and Kwan, 2017).…”
Section: Francisella-like Endosymbionts Have Been Widely Reported In mentioning
confidence: 99%